Uticaj autoverifikacije na vreme izdavanja rezultata za kliničko-hemijske i imunoesejske testove: Prvo iskustvo sa laboratorijskom autoverifikacijom - Çinpolat, Havva Yasemin (Journal of Medical Biochemistry, 2026)
Background: Auto-verification is increasingly recognized as a key tool for improving quality and efficiency in clinical laboratories. This study aimed to investigate the impact of an auto-verification system implemented for clinical chemistry and immunoassay tests on turnaround time (TAT) in a tertiary-care medical biochemistry laboratory. Methods: This study was conducted in the Medical Biochemistry Laboratory of XXX Hospital, a tertiary healthcare institution. Clinical chemistry and immunoassay tests were subjected to auto-verification using the navify® Lab Operations middleware (Roche Diagnostics, Germany) integrated with the MIA-MED Laboratory Information System (MIA Technology, Turkey). Algorithms were developed in accordance with CLSI AUTO10-A and AUTO15 guidelines, incorporating rules for quality control, serum indices, analyzer flags, delta checks, critical values, consistency checks, and analytical measurement intervals, as well as recommendations from the national health authorities. Validation of the algorithms was carried out using both simulated and patient data. The proportion of results exceeding predefined TAT targets was compared before and after auto-verification implementation with using the chi-square test. p<0.05 was considered statistically significant. Results Overall, 71% of test results and 21% of tube-based results were verified automatically. Median TAT was reduced by 6 minutes for emergency tests and 12 minutes for routine tests. The proportion of results exceeding the TAT threshold decreased significantly from 6.4% before auto-verification to 5.8% after auto-verification implementation (p < 0.001). Conclusions Auto-verification, with clearly defined and validated rules, enhances both the reliability and timeliness of laboratory results, thereby supporting quality improvement initiatives in clinical laboratories